Oestrogen receptor alpha polymorphisms in women with breast cancer and their clinical significance - Makowski, Marcin; Połać, Ireneusz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Oestrogen receptors have a wide spectrum of activity. Their prevalence in many organs suggests possible clinical ramifications. The tests that have been carried out until now do not determine whether prevalence of oestrogen receptor polymorphism has clinical significance and whether it can be put into everyday practice, especially with diagnostics and treatment of breast cancer. In this review we present a roundup of information about the influence of oestrogen receptor polymorphism on breast cancer occurrence and its clinical ramifications.